Assessing National Utilization Trends and Outcomes of Robotic and Endoscopic Thyroidectomy in the United States. (November 2020) - Jacobs, Daniel; Torabi, Sina J.; Gibson, Courtney; Rahmati, Rahmatullah; Mehra, Saral; Judson, Benjamin L.
Objective: We aimed to evaluate trends and outcomes of surgical approaches to thyroid surgery. We hypothesized that there have been changes over time in the utilization of approaches to thyroidectomy, including endoscopic, robotic, and open approaches, and that patient outcomes may differ between open surgery and endoscopic or robotic approaches. Study Design: Retrospective analysis. Setting: The National Cancer Database (NCDB) was queried between 2010 and 2016. Subjects and Methods: National cohort of patients. Descriptive statistics were performed using χ 2 test, Mann-Whitney U test, t test and analysis of variance. To investigate complication rates, patient matching was performed with subsequent analysis using simple and multivariable logistic regressions. Results: We identified 217, 938 patients within the NCDB. While endoscopic thyroid surgery increased, relatively, in use over time (0.93% to 2.34% of cases in 2010 and 2016, respectively), robotic thyroid surgery started to decline relatively to other approaches from 2013 to 2016 (0.39% to 0.25% of cases, respectively). The endoscopic approach was performed more commonly than the robotic approach within individual facilities that have reported both procedures ( P = .025). Robotic thyroid surgery was associated with increased risk of positive margins ( P = .046), while endoscopic thyroid surgery was associated with a higher rate of unplanned hospital readmission (OR, 1.55; 95% CI, 1.09-2.22), longer inpatient stays (OR, 1.55; 95% CI, 1.19-2.02), and higher 90-day postoperative mortality (OR, 4.45; 95% CI, 1.58-12.6). Conclusion: Endoscopic thyroid surgery has increased in utilization since 2004 but may have worse morbidity and mortality outcomes compared to open surgery.